Pengaruh Model Pembelajaran Expilicit Intruction Terhadap Kemampuan Guling Depan Senam Lantai - Mateley, Rinaldy M; Ponamon, Putri Kumalasari; Hamzah, Moh Aril; Djau, Selviyan; Husain, Sabrun; Hidayat, Joni Taufik; Ikhsan, Hairul; Ilham, Al (-, 2025)
This study was conducted with the aim of knowing the effect of the Explicit Instruction Learning Model on Front Roll Ability in Class VIII Students of SMP Negeri 1 Tilango. The method used in this research is an experimental method with a One-Group Pretest-Posttest Design research design. The independent variable is the Explicit Instruction Learning Model and the dependent variable is the Front Roll Ability. The sample amounted to 24 students from class VIII with the sampling technique using purposive sampling. The results of the study obtained an average pre-test value of 38.09 and an average post-test value of 43.88. The results of hypothesis testing obtained tcount ttable, namely -22.548 1.71. Thus the hypothesis that reads “There is an Effect of Expilicit Instruction Learning Model on Front Roll Ability (research study on SMP Negeri I Tilango students), can be accepted. Based on the results of this study, it can be concluded that the Expilicit Instruction Learning Model affects the Front Roll Ability of SMP Negeri I Tilango students.